Work programme 2011 - (:unkn) unknown (Publications Office of the European Union, 2011)
This work programme outlines how Cedefop will support development of European VET policy in 2011. It is divided into: (a) a narrative which reviews the policy background and then outlines how Cedefop will take forward each of its four priorities in 2011: informing European VET policies; interpreting European trends in and challenges for skills, competences and learning; assessing VET's benefits; raising the profile of VET; (b) detailed activity and project fiches. They show the expected outcomes of Cedefop's activities and the outputs of each activity's projects that will help to achieve them. Outcome indicators to measure performance of an activity are also shown in the fiches. (c) an activity-based budget (ABB) that shows the human and financial resources allocated to each activity." (Hrsg., BIBB-Doku)
Keywords: S 3.5.5.1 CEDEFOP; S 2.3 Berufsbildungspolitik; CEDEFOP; Programm; Berufsbildung; Förderung; Internationale Zusammenarbeit; Berufsbildungspolitik; Europäische Union